2020
DOI: 10.1002/ejic.201900970
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of BiOF/TiO2 Heterostructures and Their Enhanced Visible‐Light Photocatalytic Activity

Abstract: Novel BiOF/TiO2 heterostructures with controlled amounts of BiOF and TiO2 have been successfully synthesized via a simple solid‐state sintering method. The structural, morphological and optical properties were analyzed using several characterization techniques. A shift of the TiO2 absorption edge toward the visible region was observed. The optimal molar ratio of BiOF/TiO2 was found to be (1:3) with a photodegradation percentage of 91.2 % and it was 7 and 5 times more efficient than that of pure BiOF or TiO2 na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The highest photodegradation activity of TiO 2 /Fe 2 O 3 was 97.4% after 90 min. Nasr et al [ 25 ] synthesized TiO 2 /BiOF heterostructures via a solid-state sintering method. There was a slight improvement in the visible light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The highest photodegradation activity of TiO 2 /Fe 2 O 3 was 97.4% after 90 min. Nasr et al [ 25 ] synthesized TiO 2 /BiOF heterostructures via a solid-state sintering method. There was a slight improvement in the visible light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned g-C 3 N 4 and BiOF-based heterojunction results obviously portray the type-II heterojunction charge-transfer mechanism with CB and VB alignment. Therefore, the g-C 3 N 4 /BiOF heterojunction interface electrode material probably possesses the type-II mechanism of PEC water splitting , (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…Similarly, Bayan and co-workers reported that the g-C 3 N 4 /ZnO heterojunction accelerates the charge-transfer behavior under white light illumination . Moreover, Nasr et al investigated the BiOF/TiO 2 heterostructures with the band gap, CB, and VB of BiOF of 3.66, 0.20, and 3.86 eV, respectively . The above-mentioned g-C 3 N 4 and BiOF-based heterojunction results obviously portray the type-II heterojunction charge-transfer mechanism with CB and VB alignment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations